Middle School Mathematics Teachers' Beliefs and Goals regarding GeoGebra - Saralar, Ipek (2016)
This study attempted to investigate four middle school mathematics teachers’ beliefs and goals regarding dynamic mathematics software GeoGebra. Data were collected from four experienced mathematics teachers who work in public schools in four different regions of Turkey (Aegean, Marmara, Mediterranean, and Central Anatolia Regions) and teach to seventh-grade level by integrating GeoGebra into their math classes. Interviews, observation field notes, and surveys were the data collection tools used in the study. Data analysis revealed that a common belief of middle school teachers is that GeoGebra is a useful tool for teaching units which link geometry and algebra. Specifically, the majority of the participants of the study think that the most appropriate units to integrate GeoGebra in the seventh grade are Circle and Circular Regions, Linearity and Analytic Geometry. Furthermore, three fourth of the teachers stated that they incorporate GeoGebra in their classes by mostly using inquiry learning method, which provides a learning environment based more on students’ discovery. In addition to these, particular goals to use GeoGebra mentioned during the interviews were decreasing their workload, facilitating students’ learning, increasing students’ engagement, providing visual representations and saving time even though